The Role of Co-Signaling Molecules in Psoriasis and Their Implications for Targeted Treatment - Liu, Suqing; Xu, Jinhua; Wu, Jinfeng (Frontiers in Pharmacology, 2021)
Psoriasis is a chronic, systemic immune-mediated inflammatory disease manifesting in the skin, joint or both. Co-signaling molecules are essential for determining the magnitude of the T cell response to the antigen. According to the function of co-signaling molecules, they can be divided into co-stimulatory molecules and co-inhibitory molecules. The role of co-signaling molecules in psoriasis is recognized, mainly including the co-stimulatory molecules CD28, CD40, OX40, CD27, DR3, LFA-1 and LFA-3 and the co-inhibitory molecules CTLA-4, PD-1 and TIM-3. They impact the pathological process of psoriasis by modulating the immune strength of T cells, regulating the production of cytokines or the differentiation of Tregs. In recent years, immunotherapies targeting co-signaling molecules have made significant progress and shown broad application prospects in psoriasis. This review aims to outline the possible role of co-signaling molecules in the pathogenesis of psoriasis and their potential application for the treatment of psoriasis.